Abundance, Distribution Pattern and Sex Ratio of Kerang Lokan (Polymesoda expansa) in Mangrove Ecosystem of Liong River Estuary, Bantan District, Bengkalis Regency - Yosua Afrianus P; Efriyeldi '; Sofyan Husein Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on June 2015 in mangrove ecosystem of Liong River Estuary, Bantan District, Bengkalis Regency. The purpose of this research is to know abundance, distribution pattern and sex ratio of Lokan Bivalve (Polymesoda expansa). The method used was survey by observing, measuring and taking sample directly on research site. The research site was determined by purposive sampling which consisting of 3 stations, specified by mangrove densities. The result showed that average abundance were 0.44-1.66 ind/m2. The highest abundance was at Station 1 and the lowest was Station 3. The distribution pattern based on Morisita Index was aggregated. The sex ratio showed that difference among male and female at station 1 and 2, where the percentage of female was more dominating. While, sex ratio was balance on Station 3.Key words : Abundance, Sex Ratio, Distribution Pattern, Polymesoda expansa